Effect of vanadium micro-alloying on the microstructural evolution and creep behavior of Al-Er-Sc-Zr-Si alloys. (1st February 2017) - Erdeniz, Dinc; Nasim, Wahaz; Malik, Jahanzaib; Yost, Aaron R.; Park, Sally; De Luca, Anthony; Vo, Nhon Q.; Karaman, Ibrahim; Mansoor, Bilal; Seidman, David N.; Dunand, David C.
Abstract: Al-Er-Sc-Zr-Si alloys, strengthened by L12 -ordered, coherent Al3 (Er, Sc, Zr) nanoscale precipitates, can be used for automotive and aerospace applications up to 400 °C. Vanadium, due to its small diffusivity in aluminum and its ability to form L12 -ordered tri-aluminide precipitates, is a possible micro-alloying addition for further improving the service temperature of these alloys. Moreover, vanadium-containing Al3 (Er, Sc, Zr, V) precipitates are anticipated to have a smaller lattice parameter mismatch with the matrix, thereby improving the alloy's coarsening resistance. In this study, the temporal evolution of microstructural and mechanical properties of an Al-0.005Er-0.02Sc-0.07Zr-0.06Si alloy micro-alloyed with V are investigated utilizing isochronal, isothermal and double-aging treatments and compared to the results obtained from an alloy that does not contain V, but otherwise has the same composition. Both isochronal and isothermal aging treatments reveal slower precipitation and coarsening kinetics for the V-containing alloy. A peak microhardness value of ∼600 MPa is obtained after a double-aging treatment at 350 °C/16 h, followed by aging at 400 °C for 12 h. Transmission electron microscopy reveals a duplex-size precipitate microstructure, with the smaller precipitates having a mean radius <3 nm. Despite the expectation of a reduced creep resistance due to a lower precipitate/matrix lattice mismatch, both alloys have similar creep behavior at 400 °C, characterized by a threshold stress of 7.5 and 8 MPa under peak-aged and over-aged conditions, respectively. Thus, micro-additions of V to an Al-Er-Sc-Zr-Si alloy lead to enrichment of V in the Al3 (Er, Sc, Zr, V) nano-precipitates, improving their coarsening resistance without deteriorating their ability to block dislocations under creep at 400 °C. Graphical abstract: Image 1